The materialization of fear: affects and material-discursive practices in times of pandemic - Pellini, José Roberto (2022)
The Ontological Turn has proposed that subjects and objects are not fixed categories, but elements that arise within a relationship. In this sense, the world would be formed by indeterminate potentialities that are actualized in one way or another from relational phenomena. The central element in this process of actualizing the realities of the world is the affect. Unlike emotions, affect is a visceral intensity that passes between the bodies of a relationship, organizing information, resulting in the actualization of realities. This is the case, for example, of alcohol, masks, and digital materiality, which in this period of pandemic ceased to be objects to become subjects that determine and delimit our actions, behaviors and possibilities.